Social Representations of European History by the European Youth: A Cross-Country Comparison - Pierre Bouchat; Rosa Cabecinhas; Laurent Licata; Maxence Charton; Xenia Chryssochoou; Sylvain Delouvée; Hans-Peter Erb; Léo Facca; Christine Flassbeck; Valérie Haas; Nikos Kalampalikis; Renata Franc; et al. (Journal of Social and Political Psychology, 2023)
The present manuscript examines the way young Europeans represent Europe’s history. A study conducted in 11 European countries (N = 1406 students in social sciences) shows that the characters considered most important in the history of Europe are mostly men linked either to WW2, authoritarianism, or conquests and empires. Although these appear later in the rankings and despite some imbalance between countries, Europe’s history is also associated with religious figures, artists, scientists, and philosophers. These results show that the representations of the history of Europe currently shared by young Europeans correspond, in part, to historical narratives based on a specific set of experiences, events, and values supposedly common to the peoples of Europe that were promoted by European elites throughout the integration process. Further, these results suggest that beyond the negative narrative of war and the crimes of totalitarianism, the history of Europe is also embodied by positive characters transcending national boundaries and associated with a set of key elements of the EU identity: democracy, tolerance, solidarity, humanism, and the Enlightenment. Finally, we also highlight the near-total absence of characters unambiguously related to colonization and, especially, decolonization, and a strong overall under-representation of women.